Dulaglutide and pregnancy: a comprehensive safety assessment using the ex vivo placenta perfusion and in vitro models - Kuoni, Sabrina; Caviglia, Sara; Dolder, Alexandra; Gawinecka, Joanna; Ochsenbein-Kölble, Nicole; Simões-Wüst, Ana Paula (Frontiers in Pharmacology, 2026)
The use of glucagon-like peptide-1 (GLP-1) receptor agonists by young populations is rapidly increasing worldwide, thereby exposing more women of childbearing age. Dulaglutide, a long-acting GLP-1 receptor agonist designed to bind to the neonatal Fc receptor (FcRn) and approved for type 2 diabetes mellitus, reflects this trend. In this study, we wanted to evaluate transplacental passage of dulaglutide and its potential effects on placental function. Transplacental transfer was investigated both with human placenta perfusions, a model for term transfer and expressing FcRn; and with permeability assays across BeWo b30 cell layers, a model for the early pregnancy placental barrier and characterised by negligible FcRn expression. Additional in vitro experiments were performed with human placental explants and BeWo cells. Placenta perfusions revealed minimal but consistent transplacental passage of dulaglutide (0.2%–0.7%; at 1.9 nM and 19.1 nM, over 4 hours); fluorescently labelled dulaglutide was detected within foetal villi of perfused tissue, with co-localisation to the early endosome marker Rab5. Permeability assays revealed negligible transfer. Dulaglutide exposure did not impair viability, alter the secretion of pregnancy-related hormones, nor affect glycolytic metabolism neither in human placental explants nor in BeWo cells. Our results suggest that dulaglutide has no adverse effects on placental viability and functions and is not able to cross the placental barrier at earlier gestation stages. However, its ability to cross the placental barrier at term in minimal amounts, but consistently, indicates foetal exposure during late pregnancy, when FcRn is expressed.